The effects of the implementation of municipal by-laws on street vending :a case of Devenish street in Polokwane City, Limpopo, Province - Koma, Theresa Viniger Mmasechancha (My University, 2017)
The concept street vending based on the literature review revealed that it is regarded as an informal sector industry that is dominated by women. This sector is largely operated by street vendors with low skill sets and minimal education. In Africa, street vending is noticeable amongst the people who are unemployed. The Polokwane Municipality Street Vending By-Laws allow every person an opportunity to become a street vendor. The purpose of research was to investigate if the implementation of the Polokwane Street Vending By-Laws was effective in promoting a healthy and safe environment in which vendors operate. Amongst other objectives, the researcher wanted to provide possible solutions to the challenges that may be faced by the Municipality in making the implementation of by-laws effective. Qualitative and quantitative approaches were used. The data collected from street vendors operating in Devenish Street and officials of Polokwane Local Economic Development and Tourism Unit was presented and analysed. This study concludes by conferring the recommendations, conclusions and final remarks which were cautiously deduced from analysis of findings and the whole study. This followed by proposal that reflected the importance of bench marking with growing and metro cities for best practises in connection with effective implementation of local municipality street vending by-laws.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Municipal by-laws; Street vending; Ordinances, Municipal.